Anaplastic glioma: current treatment and management. (June 2015) - Le Rhun, Emilie; Taillibert, Sophie; Chamberlain, Marc C
<x xml:space="preserve">Abstract</x> Anaplastic glioma (AG) is divided into three morphology-based groups (anaplastic astrocytoma, anaplastic oligodendroglioma, anaplastic oligoastrocytoma) as well as three molecular groups (glioma-CpG island methylation phenotype [G-CIMP] negative, G-CIMP positive non-1p19q codeleted tumors and G-CIMP positive codeleted tumors). The RTOG 9402 and EORTC 26951 trials established radiotherapy plus (procarbazine, lomustine, vincristine) chemotherapy as the standard of care in 1p/19q codeleted AG. Uni- or non-codeleted AG are currently best treated with radiotherapy only or alkylator-based chemotherapy only as determined by the NOA-04 trial. Maturation of NOA-04 and results of the currently accruing studies, CODEL (for codeleted AG) and CATNON (for uni or non-codeleted AG), will likely refine current up-front treatment recommendations for AG.